ANALISIS PROTEIN DAN ASAM AMINO NATTO, MAKANAN FERMENTASI KEDELAI KUNING OLEH BASILLUS SUBTILLIS NATTO - Sahirman, Sahirman (Jurnal Ilmiah Pangan Halal, 2019)
This Research aims to analyze crude protein and amino acid profile of natto from yellow soybeans from Vedca Cianjur. Protein analysis was performed using the Semi-micro Kjeldahl method, while amino acid analysis was performed using High Performance Liquid Chromatography (HPLC). Analysis of natto paste shows that natto contains an average of 22.1% crude protein and an average amino acid content of 14.46%. The results of the analysis of 15 average amino acids in Natto with HPLC showed that amino acids consist of 7 types of essential amino acids and 8 essential amino acids.  The percentage of fresh weight of essential amino acids are Histidine (0.46% wb), Leucine (1.25% wb), Threonine (0.59%wb), Valine (0.81% wb), Methionine (0.13% wb), Isoleucine (0,76% wb), Fenilalanine (0.87% wb) and 8 non-essential amino acids are Serine (0.72% wb), Aspartic Acid (1.89%), Arginine (0.91%), Lysine (0.83% ), Glutamine (3.62%), Glycine (0.65%), Alanin (0.67%), and Tyrosine (0.3% wb). Glutamine is the highest level of amino acids (3.62% wb), followed by aspartic acid (1.89% wb) and Leucine (1.25% wb).